2006
DOI: 10.1139/z06-134
|View full text |Cite
|
Sign up to set email alerts
|

Songbird response to seismic lines in the western boreal forest: a manipulative experiment

Abstract: Millions of kilometres of seismic lines have been created for hydrocarbon exploration in the boreal forest and their impact on songbirds is unknown. I conducted a replicated before–after control–impact (BACI) field experiment in southern Northwest Territories to evaluate the impact of 6 m wide seismic lines on songbirds. Territories of all birds on six pairs of 12 ha control and treatment plots were mapped for one year before and one year after seismic lines were cut through the treatment plots. The songbird c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 26 publications
1
50
1
Order By: Relevance
“…Although forest clearing for oil and gas development reduces the amount of trees on the landscape, the effects of fragmentation from linear features and small disturbances (e.g., well sites) were not important predictors of Canada Warbler abundance in this study. Machtans (2006) found that Canada Warblers did not avoid seismic lines in the Northwest Territories but included these features within their territories. However, linear features were treated as unusable, and territory size was expanded to compensate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although forest clearing for oil and gas development reduces the amount of trees on the landscape, the effects of fragmentation from linear features and small disturbances (e.g., well sites) were not important predictors of Canada Warbler abundance in this study. Machtans (2006) found that Canada Warblers did not avoid seismic lines in the Northwest Territories but included these features within their territories. However, linear features were treated as unusable, and territory size was expanded to compensate.…”
Section: Discussionmentioning
confidence: 97%
“…However, studies also report the Canada Warbler in early seral vegetation with brushy edges and residual patches of live trees , Schieck and Hobson 2000, Schieck and Song 2006; reviewed by Reitsma et al 2010). Canada Warblers also may not avoid edges created by human development, but may increase territory size and incorporate smaller clearings within their defended space (Machtans 2006). Clearly, refined understanding of the local habitat needs of Canada Warblers and how these are influenced by various types of human activities that alter the age structure, spatial pattern, and composition of their habitat is needed, particularly at large spatial extents.…”
Section: Introductionmentioning
confidence: 99%
“…Forest regeneration occurs in many energy sector disturbances; however, human use often keeps seismic lines and pipelines open (Figure 1). Soil compaction and mixing from construction and ground disturbance, as well as shading by surrounding vegetation, also inhibit tree regeneration (Lee andBoutin 2006, Lankau et al 2013; but see Machtans 2006). Unlike forestry, where tree planting and natural regeneration result in rapid regrowth, changes in boreal forest bird habitat may persist for years in many types of energy sector disturbance (Lee andBoutin 2006, Lankau et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Industrial activity peaked in 1995-2000 and has been essentially nonexistent since 2007. Most of that disturbance produced small effects that a regional study like ours would not detect (Machtans 2006). Finally, we collected detailed vegetation data twice during our study, separated by 11 years, and succession was not changing the study stands in any significant way (C. S. Machtans, unpublished data).…”
Section: Local Habitat Issuesmentioning
confidence: 90%